2020
DOI: 10.1093/cid/ciaa955
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 Antibody Prevalence in Blood in a Large School Community Subject to a Coronavirus Disease 2019 Outbreak: A Cross-sectional Study

Abstract: Abstract Background A SARS-CoV-2 outbreak affecting 52 people from a large school community in Santiago, Chile was identified (March 12), nine days after the first country case. We assessed the magnitude of the outbreak and the role students and staff played using a self-administered antibody detection test and survey. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
1
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(145 citation statements)
references
References 15 publications
4
133
1
7
Order By: Relevance
“…Cross-sectional studies estimated the proportion of SARS-CoV-2 positive cases, to give an insight into how many people have been infected in schools. As described above, the positivity results in the general study population under school environment varied from 0.00 (lowest in eight daycare centers in Belgium) to 25.87% (highest in one high school in France), which is likely to reflect the community positivity rate at the time the study was conducted [18][19][20][21][22][23]. The lower positivity rate in students suggested that students are less susceptible to infection and/or less frequently infected than adult school staff, which indicated that students are not at higher risk of causing super-spreading events in schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies estimated the proportion of SARS-CoV-2 positive cases, to give an insight into how many people have been infected in schools. As described above, the positivity results in the general study population under school environment varied from 0.00 (lowest in eight daycare centers in Belgium) to 25.87% (highest in one high school in France), which is likely to reflect the community positivity rate at the time the study was conducted [18][19][20][21][22][23]. The lower positivity rate in students suggested that students are less susceptible to infection and/or less frequently infected than adult school staff, which indicated that students are not at higher risk of causing super-spreading events in schools.…”
Section: Discussionmentioning
confidence: 99%
“…A large school community was closed on 13 March in Chile (Santiago) and during quarantine, a homedelivery and self-administered antibody test were conducted among 1,009 students and 235 school staff [19]. Antibody positive rates were 9.91% (100/1009) and 16.60% (39/235) respectively.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…Latin-America is one of the most affected regions of the world by the pandemic [9], with peak cases occurring between July 20 and August 16 [10]. Although some studies from Latin-American countries evaluating serology in the general population [11,12] or schools have been published [13,14], to our knowledge only one study in an oncology unit in Brazil [15] has assessed seroprevalence in HCW. Our study was performed during a very active increase of SARS-CoV-2 infections in our country and city: during the five weeks of the study 248,205 new cases were identified in Colombia (109,505 vs. 357,710) and 93,907 of these were in Bogotá (34,131 vs. 128,038) (http://saludata.saludcapital.gov.co/osb/index.php/datos-de-salud/enfermedadestrasmisibles/covid19/ page consulted 08 /19/20).…”
Section: Introductionmentioning
confidence: 99%
“…To determine if having a history of mask-wearing reduced seropositivity, we constructed a directed acyclic graph (DAG) based on existing literature evidence and identified gender, age, travel history, school type, and role at LCSC as potential confounders to control for in the multivariable logistic regression ( Supplementary Figure 1). 6,15 Finally, backward-stepwise feature elimination was used to identify the features most predictive of seropositivity in a multivariable logistic regression starting with the thirteen categories queried in the survey (threshold p -value of 0•05). After the model was identified for which all factors were statistically significant, three factors (mask history, travel history, and symptom history) which are understood based on external studies to have an impact on infectivity were reintroduced to this reduced model.…”
Section: Discussionmentioning
confidence: 99%